Peran Pemerintah Dalam Menangani Infrastruktur Perbatasan Negara Yang Masih Terbatas - Maria Yovita Naif; Karolus Kevin Sylton Mahe; Monika Prisila Sarah; Veren Victoria Dangga; Yohanes Arman (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Many countries with limited borders face serious challenges in developing adequate infrastructure. Factors such as difficult topography, limited access to resources, and conflict or tension at borders can weigh on effective infrastructure development. Therefore, the role of government is very important in overcoming these obstacles. Research Methods Meta-Analysis : This method involves statistical analysis of the results of research that has been done before. Meta-analysis collects data from several studies to obtain stronger and general conclusions. Constraints on State Border Infrastructure: the government can seek solutions through regional and international cooperation, proper budget allocation, regulatory adjustments, political dialogue, and active participation of the community in decision-making processes decisions. The Government's Role in Overcoming Limited Infrastructure, With a comprehensive approach and involving various stakeholders, the government can overcome the constraints of border infrastructure development which are still limited. The following are some of the roles that can be played by the government: Infrastructure Planning: The government must carefully plan the infrastructure development of the country's borders. This involves needs assessment, risk analysis, and development of long-term plans to ensure the border infrastructure can meet future demands. Overall, the government's role in handling state border infrastructure is still very important in maintaining national security, law, supporting the economy, managing migration and resources, strengthening relationships, and overcoming disasters. By prioritizing good and sustainable investment and planning by mobilizing all related components or stakeholders to be able to fulfill benefits and achieve goals so that the government can ensure that the basic infrastructure becomes a strong foundation for the progress of the country as a whole.